The Effect of Rainfall Intensity on Soil Erosion and Runoff for Latosol Soil in Indonesia - Sukandi Sukartaatmadja; Yohei Sato; Eiji Yamaji; Masaya Ishikawa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
Soil erosion is the most serious problem of land degradation in Indonesia. However, limited report has been documented. The erosion problem in Indonesia, particularly in Java, has been at an alarming rate. The fundamental 1 case of soil erosion is the rain effect upon the soil. Rainfall intensity and soil characteristics are related to soil erosion  and runoff The objective of this research was to study the relationship of rainfall intensity, soil erosion and runoff in latosol soil. An experiment was conducted using plot size 22 m in length and 2 m in width and 9 % slope. A field experiment was conducted with rainfall intensity observation for 3 months, to collect soil erosion and runoff in the soil collector. A laboratory experiment was done using rainfall simulator instruments with rainfall intensity of 2.3, 3.4, 4.5, 5.6 cm/hr and 8 % slope each with 3 replications. The result of the experiments showed that soil erosion was 3. J 4 t/ha and runoff was 33.20 m3/ha. When the rainfall size increased the soil erosion and runoff also increased. The correlation coefficient between £130 (Interaction 130 and energy) and soil erosion was positive. Key Words: Rainfall intensity, Soil erosion, Latosol soil